Retinopathy of prematurity in a tertiary facility: an initial report of a screening programme (2020)
Retinopathy of prematurity (ROP) screening in Nigeria is at a nascent stage and at the moment there are no National guidelines for ROP screening in Nigeria. Thus it is desirable for screening programs to report findings amongst screened preterm infants in order to facilitate the development of national ROP screening criteria and guidelines. The aim of this report is to describe the frequency, severity and risk factors for retinopathy of prematurity (ROP) among preterm and very low-birth-weight babies screened within the first year of initiating an ROP screening program at a Nigerian tertiary facility. Methods: A cross-sectional study of infants born at less than 34 weeks gestational age; or with birth weight less than 1500g between May 2016 and May 2017. ROP screening examinations were performed by ophthalmologists with the use of an indirect ophthalmoscope, after pupillary dilation, in collaboration with the neonatology team. Information on gestational age at birth, birth weight, oxygen therapy and presence of other risk factors were recorded and analyzed. Results: A total of 74 infants were screened during the period. There were 36 (48.6%) males. Mean gestational age at birth was 29.6 (±2.35) weeks. Mean birth weight was 1.26 (±0.27) kg with a range of 800 to 1950g. ROP was detected in 9 (12.2%) infants. Two (22.2%) of these had Threshold ROP. There was no significant difference between the mean birth weight and mean gestational age of the infants who had ROP compared to those without ROP. The two infants with Threshold ROP were treated with intravitreal Bevazicumab and had regression of ROP. Conclusion: Retinopathy of prematurity was diagnosed in at risk infants in this facility. There is, therefore, a need to establish ROP screening programs in all neonatal units across the country. In addition, established programs need to evaluate their screening criteria with a view towards developing country-specific screening guidelines.